Husband Support For The Implementation Of Antenatal Care In Primigravid Pregnant Women In Bpm Ny”N” Tambak Rejo Village, Waru District, Sidoarjo District Year 2020 - Siti Rofiatun; Atik Setiawan Wahyuningsih (Master of Public Health Program Universitas STRADA Indonesia, 2023)
The health of pregnant women is one of the important aspects to consider in a woman's life cycle because during her pregnancy unexpected complications can occur. Every pregnant woman will face risks that can threaten her life. Therefore, every pregnant woman needs care during her pregnancy (Salmah, 2016). The purpose of this study was to determine the influence of husband's support on the implementation of Antenatal Care in primigravida pregnant women at BPM NY